Iodine-catalyzed diazo activation to access radical reactivity - Pan Li (Nature Portfolio, 2018)
Radical reactivity of diazo compounds, useful organic building blocks, is yet underexplored. Here, the authors report an iodine-catalyzed radical activation of diazo compounds affording a variety of substituted cyclopropanes, pyrroles and epoxides under either thermal- or photo-initiated conditions.